Antidepressants and memory effects of ketamine under the neuromolecular view: A literature review - Da Silva GP Felipe; Rezende M Gabriel; Lohana Pompelli Scapatici; Luísa Zanelatto de Araujo; Bruna Carrara Lombardi; Caroline Vidal; David Batista Wiedmer; Lucas Schoeler; Minhoto R Gisele; Andreatini Roberto (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Objective: Major Depressive Disorder (MDD) has as diagnostics characteristics chronic deep sadness, anhedonia, sleeping disorder, lower energy, and cognition impairment like memory deficits. Among the pharmacological treatments that have been used until the moment, most of them act by monoaminergic pathways. Overall, the antidepressant effects promoted by this kind of medication usually delay starting, resulting in treatment resistance by the patients; moreover, in some cases, this kind of treatment has shown to be inefficient in depression remission. With this, new treatments have been studied for resistant cases and an immediate antidepressant effect, for example, ketamine - whose action occurs in glutamatergic pathways. This study aimed to analyze, from a literature review, the molecular mechanisms involved in the action of ketamine - focusing on the neuroplastic hypothesis of depression.  Methods: A literature search was conducted in PubMed, MEDLINE, and SciELO databases using the following terms as descriptors: "ketamine AND depression AND neuroplasticity," with criterion PICO, resulting in 60 bibliographic texts.  Results/discussion: The studies analyzed demonstrated that ketamine could exert its antidepressant effects through the inhibition of GABAergic interneurons, activation of TRK-B/AKT/mTORC pathways involved with cell survival/growth through the neurotrophine BDNF and increased activation of AMPAr by glutamate. Furthermore, it is evident that the pharmacodynamics of ketamine involves different molecular cascades present in the impaired neural plasticity pathways in individuals with MDD.  Conclusion: Thus, more research on the effectiveness of ketamine is needed to consolidate its use in MDD and to evolve with glutamatergic pharmacological therapy for other mental disorders, such as bipolar and neurodegenerative affective disorders, an example of Alzheimer's disease.